1987
DOI: 10.1001/jama.1987.03400180089033
|View full text |Cite
|
Sign up to set email alerts
|

Low Fetal Loss Rates After Ultrasound-Proved Viability in Early Pregnancy

Abstract: Once pregnancy is recognized clinically, it is accepted that 12% to 15% undergo spontaneous abortion. However, the actual time of fetal demise has not yet been determined. To address this question, the outcomes of pregnancies identified before 21 days of conception by serum beta-human chorionic gonadotropin assays were studied. All subjects underwent ultrasound examinations at eight and 12 weeks' gestation. Among 220 women who had a viable pregnancy at eight weeks, only seven (3.2%) experienced a fetal loss th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…After experiencing a loss, couples desire information about future risk of subsequent pregnancy loss. Whereas current practices of ultrasonography are extensively utilized to predict real-time pregnancy viability (4), less is known about preconception biomarkers to predict the risk of loss in a future pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…After experiencing a loss, couples desire information about future risk of subsequent pregnancy loss. Whereas current practices of ultrasonography are extensively utilized to predict real-time pregnancy viability (4), less is known about preconception biomarkers to predict the risk of loss in a future pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…It frequently occurs during the first 12 weeks of pregnancy. Abortus imminens affects approximately 20-50% of all pregnancies 1 and it may cause abdominal cramps or pelvic pain. Recent studies clearly demonstrated that there is an increased risk of adverse pregnancy outcomes such as preterm delivery, low birth weight, and perinatal death in AI pregnancies.…”
mentioning
confidence: 99%